2015
DOI: 10.1371/journal.pone.0131133
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting-State Brain Activity and Connectivity in Depressed Parkinson’s Disease

Abstract: Depressive symptoms are common in Parkinson’s disease (PD), but the neurophysiological mechanisms of depression in PD are poorly understood. The current study attempted to examine disrupted spontaneous local brain activities and functional connectivities that underlie the depression in PD. We recruited a total of 20 depressed PD patients (DPD), 40 non-depressed PD patients (NDPD) and 43 matched healthy controls (HC). All the subjects underwent neuropsychological tests and resting-state fMRI scanning. The betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 31 publications
2
58
0
1
Order By: Relevance
“…Moreover, a recent study demonstrated altered connectivity in the posterior cingulate cortex/precuneus in PD patients with depression compared to PD without depression [23], and our results may indicate the structural basis of these functional changes in D-PD.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, a recent study demonstrated altered connectivity in the posterior cingulate cortex/precuneus in PD patients with depression compared to PD without depression [23], and our results may indicate the structural basis of these functional changes in D-PD.…”
Section: Discussionsupporting
confidence: 65%
“…After initially screen of the titles and abstracts, 17 ALFF studies were potentially eligible for this meta-analysis. Of these, 6 studies were excluded because of the following reasons: one was an abstract41; one used a method of regions of interest42; one applied an approach of support vector machine training43; one did not perform a direct comparison between PD patients and healthy controls16; and two just reported findings from the on-state of PD patients2244. The remaining 11 studies were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal prefrontal-limbic network connectivity has been demonstrated in depressed PD patients [31, 42]. PD patients with depression are associated with disrupted functional connectivity between the median cingulate cortex and precuneus, prefrontal cortex, and cerebellum [43]. The cingulate cortex plays key roles in integrating multimodal information that is important for emotional, sensorimotor, and cognitive functions [44].…”
Section: Non-motor Symptomsmentioning
confidence: 99%
“…Progressive micrographia was also associated with disconnections between the pre-SMA, rostral cingulated motor area and cerebellum18 controlsWu T et al, 2015 [22, 29]22 PD patientsVisuomotor association taskEffective connectivityGranger causality analysis (GCA)The connectivity from the putamen to the motor cortex was decreased in PD22 controlsMa H et al, 2015 [30]50 PD patientsResting stateFunctional connectivityThe bilateral dentate nucleus had higher connectivity with the bilateral cerebellar anterior lobe, and lower connectivity with the bilateral prefrontal cortex in tremor-dominant PD29 age-matched health controlsTessitore A et al, 2012 [32]29 PD patientsResting stateFunctional connectivityReduced connectivity within both executive-attention and visual networks15 controlsLiu H et al, 2013 [34]9 PD patientsResting stateFunctional connectivityDecreased connectivity of the dentate nucleus with the bilateral cerebellar posterior lobe in tremor-dominant PD9 controlsHu X et al, 2015 [35, 43]21 tremor-dominant (TD)-PDResting stateVoxel-mirrored homotopic connectivity (VMHC)TD-PD exhibited significantly lower VMHC values in the posterior lobe of the cerebellum. AR-PD exhibited lower VMHC values in the precentral gyrus.29 akinetic-rigid (AR)-PD patients26 controlsSeibert TM et al, 2012 [36]19 cognitively unimpaired controls, 19 cognitively unimpaired PD patients,Resting stateFunctional connectivityDecreased striato-prefrontal connectivity in patients with dementia18 patients with dementiaGorges M et al, 2015 [37]14 cognitively unimpaired PD patients, 17 cognitively impaired PD patientsResting stateFunctional connectivityDecreased default mode network connectivity in cognitively impaired PD patients.22 controlsDisbrow EA et al, 2014 [38]14 non-demented PD patients, 20 controls.Resting stateFunctional connectivityDecreased default mode network connectivity in PDManza P et al, 2016 [41]62 early-stage PD patientsResting stateFunctional connectivityMot...…”
Section: Introductionmentioning
confidence: 99%